2022
DOI: 10.21608/edj.2021.106576.1873
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Light-Activated Calcium Silicate Versus Calcium Hydroxide on Permanent Carious Molars Treated With Step-Wise Excavation: A Randomized Clinical Trial

Abstract: Aims and Objectives: to evaluate the antibacterial action of Theracal (light-cured calcium silicate) liner in comparison to Biner LC (light-cured calcium hydroxide) liner on permanent carious molars treated with step-wise excavation in 6 months follow-up. Materials and Methods:A total of 48 patients were assigned in this study. Participants were divided into two groups randomly according to the type of liner that was placed and sample of dentin that will be taken before placement of liner and after placement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Regarding sealing ability, an in vitro study showed that TheraCal LC had a significantly higher internal gap at the dentinal surface when compared to MTA and Biodentine; however, MTA and Biodentine had comparable results in sealing ability [ 37 ]. Concerning the microbiological effect, a randomized clinical study was conducted using permanent carious molars treated with indirect capping and found that the reduction of the bacterial count in both Streptococcus mutans and Lactobacillus was using Biner LC (light-cured hydroxy calcium phosphate) or TheraCal LC [ 38 ]. Moreover, in vivo subcutaneous implantation test performed in rats showed irregular collagen formation and tissue inflammation; such study informed that inflammation in the liver and kidney tissue of the rats was more severe with the use of TheraCal LC, possibly attributable to the light-cured compounds [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sealing ability, an in vitro study showed that TheraCal LC had a significantly higher internal gap at the dentinal surface when compared to MTA and Biodentine; however, MTA and Biodentine had comparable results in sealing ability [ 37 ]. Concerning the microbiological effect, a randomized clinical study was conducted using permanent carious molars treated with indirect capping and found that the reduction of the bacterial count in both Streptococcus mutans and Lactobacillus was using Biner LC (light-cured hydroxy calcium phosphate) or TheraCal LC [ 38 ]. Moreover, in vivo subcutaneous implantation test performed in rats showed irregular collagen formation and tissue inflammation; such study informed that inflammation in the liver and kidney tissue of the rats was more severe with the use of TheraCal LC, possibly attributable to the light-cured compounds [ 39 ].…”
Section: Discussionmentioning
confidence: 99%